"Because We Are Peers, We Actually Understand": Third‐Party Participant Assistance in English as a Lingua Franca Classroom Interactions. Issue 4 (1st February 2018) - Matsumoto, Yumi
Abstract : This study qualitatively investigates miscommunication moments during which a teacher of English who speaks a first language other than English and students with various linguacultures collaboratively resolve communicative problems with the assistance of other students in the classroom. These other students, referred to as third‐party participants because they are not originally part of the miscommunication phenomena, help resolve miscommunication by sharing their interpretations of what their peers say. Combining sequential analysis with ethnographic information, this study examines how students as third‐party participants take initiative in resolving miscommunication by representing their peers' viewpoints and how teachers elicit assistance from these third‐party participants. The analysis reveals that third‐party participants' repair efforts can be effective in multilingual classrooms in various ways, including helping to save face among interlocutors involved in miscommunication, negotiating meaning, creating active class participation patterns, and engendering the class norm that dealing with miscommunication and achieving mutual understanding are everyone's responsibility in multilingual classrooms. The analysis also demonstrates the important role of nonverbal elements (e.g., gaze, smile, and gesture) for enhancing explicitness in English as a lingua franca communication. This study suggests recommendations for second language teacher education regarding the need for second language teachers to develop a mindset for intercultural, multilingual classrooms.